2006
DOI: 10.1152/ajpgi.00172.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of intestinal sterol transporters Abcg5, Abcg8, and Npc1l1 in cholesterol absorption in mice: gender and age effects

Abstract: Recent studies have indicated that intestinal cholesterol absorption is a multistep process, which is regulated by multiple genes at the enterocyte level. However, the molecular mechanisms whereby there are gender differences in intestinal cholesterol absorption efficiency and the efficiency of cholesterol absorption increases with age have not yet been fully understood. To explore whether aging increases cholesterol absorption via intestinal sterol transporters, we studied the higher cholesterol-absorbing C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 39 publications
4
60
1
3
Order By: Relevance
“…Duan et al [67] showed that estrogens may influence cholesterol uptake through up-regulation of NPC1L1 and possibly by down-regulation of the sterol efflux transporters ABCG5 and ABCG8. It was suggested that estrogen acts as transcription modulator for the target genes through effects on estrogen receptor (ER) a or ER b, two subtypes of the steroid hormone receptor superfamily.…”
Section: Gender and Age Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Duan et al [67] showed that estrogens may influence cholesterol uptake through up-regulation of NPC1L1 and possibly by down-regulation of the sterol efflux transporters ABCG5 and ABCG8. It was suggested that estrogen acts as transcription modulator for the target genes through effects on estrogen receptor (ER) a or ER b, two subtypes of the steroid hormone receptor superfamily.…”
Section: Gender and Age Differencesmentioning
confidence: 99%
“…It was suggested that estrogen acts as transcription modulator for the target genes through effects on estrogen receptor (ER) a or ER b, two subtypes of the steroid hormone receptor superfamily. Furthermore, a significant positive effect of aging on cholesterol uptake through inhibition of the sterol efflux transporters ABCG5 and ABCG8 has been reported [67]. In contrast, fat uptake was suggested to decline with ageing [68,69,70] and also more recently decreased ileal uptake of palmitic, stearic, oleic and linoleic acid was found with ageing in rats [71].…”
Section: Gender and Age Differencesmentioning
confidence: 99%
“…Ezetimibe is an inhibitor of Niemann-Pick C1-Like 1 transporter (NPC1L1) in the jejunal brush border, thus decreasing intestinal cholesterol absorption and reducing total and LDL-cholesterol levels [27,28]. Although, to the best of our knowledge, no data are available in humans, aging was associated with up-regulated expression of NPC1L1 in mice [29]. However, the lack of correlation between ezetimibeinduced changes in plasma lipids and the impact of this drug on plasma hsCRP, leptin, and adiponectin suggests that non-lipid-related effects of ezetimibe are responsible for its different effect on systemic inflammation and adipose disuse in various age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lally et al en ratas Sprague -Dawley, a las que se indujo diabetes mediante estreptozotocina, investigaron el efecto de una dieta estándar de laboratorio a la que se adicionó un 40% de grasa y 0,5% de colesterol, en la expresión de NPC1L1, ABCG5 y ABCG8, demostrando un incremento neto en la absorción de colesterol a través de la sobrerregulación de NPC1L1 y una represión de ABCG5 y G8 en el hígado e intestino. Duan et al (2006), estudiaron el efecto de la edad en la absorción de colesterol en ratones C57L/J (caracterizados por su alta absorción de colesterol) y ratones AKR/J (caracterizados por absorber poco colesterol). Los animales fueron mantenidos consumiendo una dieta estándar de laboratorio y estudiados a las 8 semanas (adultos jóvenes), 36 semanas (adultos mayores) y 50 semanas (ancianos) de edad, respectivamente.…”
Section: Discussionunclassified
“…15 ratones machos C57BL/6 fueron divididos en grupos de cinco, sometidos a 15 días de adaptación con ciclos de 12 horas de luz y oscuridad y alimentados a libre acceso con la dieta rata de laboratorio (Champion S.A.). Luego, a cinco de los animales se les extrajo sangre para medir los lípidos plasmáticos y extirpó el intestino delgado, para evaluar la expresión basal génica y proteica de NPC1L1, ABCG5 y ABCG8 (Duan et al, 2006). A los 10 animales restantes se les indujo hipercolesterolemia, alimentándolos por 4 semanas, a libre acceso con la dieta tipo Paigen; D12336 (Paigen et al, 1985).…”
Section: Materials Y Métodosunclassified